Aggression, Academic Behaviors, and Popularity Perceptions Among Boys of Color During the Transition to Middle School. (29th July 2013) - Xie, Hongling; Dawes, Molly; Wurster, Tabitha J.; Shi, Bing
Abstract : The transition to middle school often presents behavioral and academic challenges to youths. Boys of color (i.e., African American and Hispanic in this study) may be especially vulnerable. In this study, peer nominations of aggressive and academic behaviors as well as youths' perceptions of how these behaviors were related to popularity in peer networks were obtained from the spring semester of fifth grade through the spring semester of seventh grade, with the transition occurring as the students entered the sixth grade. The sample included 188 boys (71 Caucasian, 90 African American, and 27 Hispanic) from an urban school district in the northeastern United States. Trajectory analyses showed that African American boys scored lower in studentship and higher in rule‐breaking and aggressive (both physical and social) behaviors prior to the transition, and such differences among ethnic groups were largely maintained during the transition. Hispanic boys displayed decreases in their studentship during the transition. African American boys' perception of how studentship affects popularity was more positive than other boys prior to the transition, but it decreased during the transition. African American boys also endorsed rule breaking and physical and social aggression more positively for popularity prior to the transition, whereas Caucasian and Hispanic boys' endorsement increased during the transition and eventually caught up with those of African American boys in seventh grade. A positive within‐individual association was found between youths' popularity perception and their behavior for studentship, rule breaking, and physical aggression, which did not differ by ethnicity.